2017
DOI: 10.1111/hex.12642
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐initiated recruitment for clinical research: Evaluation of an outpatient letter research statement

Abstract: Background UK Hospital Trusts are charged with increasing patients’ research awareness and willingness to take part in research. This includes implementing strategies to encourage patient‐initiated enquiries about participation.ObjectivesTo evaluate the impact of a research statement inserted in outpatient letters in one clinical service, and to derive suggestions on potential steps towards increasing patient‐initiated recruitment.SettingA medical outpatient clinic of a research‐active hospital trust, serving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Notions of benefit and risk are likely to change over time, both for a specific individual and within the context of a given institution. Ongoing conversations about the risks and benefits of participation, and what the idiom research refers to, will be critical to achieving adequate engagement and ensuring that willingness to participate is not confounded with a need for care [64,65]. Furthermore, potential users of health care services may anticipate receiving further and/or advanced treatment for long-term and rare diseases.…”
Section: Ethicsmentioning
confidence: 99%
“…Notions of benefit and risk are likely to change over time, both for a specific individual and within the context of a given institution. Ongoing conversations about the risks and benefits of participation, and what the idiom research refers to, will be critical to achieving adequate engagement and ensuring that willingness to participate is not confounded with a need for care [64,65]. Furthermore, potential users of health care services may anticipate receiving further and/or advanced treatment for long-term and rare diseases.…”
Section: Ethicsmentioning
confidence: 99%
“…Reported 'barriers' to participation include: organisational factors, lack of training, lack of eligible patients, lack of patient trust in clinical research and expectation of harm (Ford et al 2008, Treweek et al 2010. Our findings from two surveys (McKevitt et al 2015, Wienroth et al 2018 among clinical populations suggest that low awareness of what 'research' is and what research participation means are also important factors.…”
Section: Introductionmentioning
confidence: 82%
“…The NIHR itself claims that involvement of the public in developing and governing research contributes to the effectiveness and efficiency of both research and the patient recruitment process into clinical research itself (2015: 8). These framings, forming part of the NIHR imaginary of patients and publics in research, do not necessarily reflect public understanding of research participation and involvement, as findings from surveys of patients about clinical research have shown (Adam et al 2015, McKevitt et al 2015, Wienroth et al 2018.…”
Section: Assetisation As Valuation Practicementioning
confidence: 99%
See 1 more Smart Citation